The Effectiveness of the Role of Agricultural Extension Workers to Increase Rice Paddy Productivity in Asahan Regency - Eryanto, Oktoni; Kuswardani, Retno Astuti; Noer, Zulheri; Nasution, Anisah; Siregar, Mawaddah Putri Arisma (Universitas Galuh, 2024)
Asahan Regency occupies the 13th position out of 33 regencies/cities as a rice producer in North Sumatra Province the rice productivity results are relatively low so that it is a problem that needs to be resolved. Agricultural extension workers act as motivators, educators, facilitators and communicators. This study aims to determine and analyze the influence of the role of agricultural extension agents on the productivity of paddy rice in Asahan Regency. The study was conducted in Asahan Regency, North Sumatra Province using primary data obtained from direct surveys and secondary data as supporting data using the Stratified Proportional Random Sampling method. The respondents were farmers from 3 sub-districts, namely Rawang Panca Arga, Sei Kepayang and Meranti districts. Data analysis using description analysis and Partial Least Square (PLS).